2020
DOI: 10.1088/1674-4926/41/10/101301
|View full text |Cite
|
Sign up to set email alerts
|

Silicon photonic transceivers for application in data centers

Abstract: Global data traffic is growing rapidly, and the demand for optoelectronic transceivers applied in data centers (DCs) is also increasing correspondingly. In this review, we first briefly introduce the development of optoelectronics transceivers in DCs, as well as the advantages of silicon photonic chips fabricated by complementary metal oxide semiconductor process. We also summarize the research on the main components in silicon photonic transceivers. In particular, quantum dot lasers have shown great potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…However, this example shows the potential interest of silicon photonics sensors that, indeed, have been widely used for various specific targets. Reviews can be found in [20,[123][124][125].…”
Section: Microring-based Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…However, this example shows the potential interest of silicon photonics sensors that, indeed, have been widely used for various specific targets. Reviews can be found in [20,[123][124][125].…”
Section: Microring-based Sensormentioning
confidence: 99%
“…Since this review of silicon photonics is quite a personal history and a story of my contributions to the field, almost all the cited works refer to my own papers. The interested reader can find relevant literature in the original papers or in other recent reviews [12][13][14][15][16][17][18][19][20][21][22][23][24]. At the end of each subsection, I cite few references where recent contributions to the related field are reported.…”
Section: Introductionmentioning
confidence: 99%
“…18−23 In the fabrication of WS 2 -based silicon photonic devices, it is inevitable to contact WS 2 directly with the silicon, whether it be the silicon substrate, silicon waveguides, 24,25 or siliconbased devices. 26,27 Consequently, the WS 2 /Si interfaces are naturally formed in this process. The WS 2 /Si interface would play a very important role in WS 2 -based optoelectronic devices due to the interfacial complex effects and abundant states, 28−30 such as charge transfer, 31,32 dielectric screening, optical interference effects, and surface charge states.…”
Section: Introductionmentioning
confidence: 99%
“…In the fabrication of WS 2 -based silicon photonic devices, it is inevitable to contact WS 2 directly with the silicon, whether it be the silicon substrate, silicon waveguides, , or silicon-based devices. , Consequently, the WS 2 /Si interfaces are naturally formed in this process. The WS 2 /Si interface would play a very important role in WS 2 -based optoelectronic devices due to the interfacial complex effects and abundant states, such as charge transfer, , dielectric screening, optical interference effects, and surface charge states. , First, the charge transfer induced by the difference of Fermi level between substrate and monolayer WS 2 can impact the contribution of neutral excitons and charged trions to the photoluminescence (PL) and Raman modes. , Moreover, it was reported that the interlayer exciton generated by the charge transfer from the Si substrate to WS 2 could broaden the infrared response range of the photodetector up to 3043 nm .…”
Section: Introductionmentioning
confidence: 99%
“…Silicon photonics has emerged as a powerful technology for optical networks in datacom and computercom with the commercial success of silicon photonic transceivers [1][2][3]. In the past decade, silicon photonics has been rapidly matured with the process standardization and the process design kit (PDK) development of silicon photonic foundries [4,5].…”
Section: Introductionmentioning
confidence: 99%